VD_FINDINFO ML / 2013 / 199 vom 10. Juli 2013 - VD Tribunal cantonal (2013)
DROIT D'ÊTRE ENTENDU, NOTIFICATION IRRÉGULIÈRE, NULLITÉ | 84 al. 2 LP, 136 CPC (CH), 138 al. 1 CPC (CH), 138 al. 3 let. a CPC (CH), 253 CPC (CH), 256 al. 1 CPC (CH), 53 CPC (CH)